Effects of prone versus supine position during enteral nutrition on clinical outcomes and complications in mechanically ventilated patients: a systematic review and meta-analysis - Zhao, Mei-Ling; Hou, Yun-Feng; Zong, Li-Wu; Yue, Yi-Feng; Ma, Shuang (Frontiers in Nutrition, 2026)
BackgroundEnteral nutrition (EN) is routinely employed in mechanically ventilated patients, including those undergoing prone positioning for severe respiratory failure. However, the impact of body positioning during EN on clinical and nutritional outcomes remains unclear. This systematic review and meta-analysis aimed to evaluate the effects of prone versus supine positioning during EN on caloric intake and related complications.MethodsA comprehensive literature search was conducted in PubMed, The Cochrane Library, Web of Science, Embase, WanFang Data, CNKI, and SinoMed through June 16, 2025. Eligible studies included randomized controlled trials and cohort studies comparing EN outcomes between prone and supine positioning in adult mechanically ventilated patients. Data extraction, quality assessment (Newcastle–Ottawa Scale), and meta-analyses were performed in accordance with PRISMA guidelines.ResultsFive studies comprising 319 patients were included. Prone positioning was associated with significantly lower caloric intake (SMD = −1.31, 95% CI: −2.43 to −0.18), higher odds of vomiting (OR = 2.31, 95% CI: 1.63–3.26), high gastric residual volume (OR = 2.72, 95% CI: 1.47–5.03), ventilator-associated pneumonia (OR = 2.31, 95% CI: 1.34–3.99), and EN interruption (OR = 4.75, 95% CI: 2.22–10.17). No significant difference in mortality was observed (OR = 1.11, 95% CI: 0.65–1.88). No publication bias was detected.ConclusionCompared to the supine position, EN during prone positioning is associated with reduced nutritional intake and increased gastrointestinal and pulmonary complications. Optimized feeding protocols are warranted to ensure safe and effective nutritional support in prone-ventilated patients.